Nucleolar disruption in dopaminergic neurons leads to oxidative damage and Parkinsonism through repression of mammalian target of rapamycin signaling - Rieker, Claus; Engblom, David; Kreiner, Grzegorz; Domanskyi, Andrii; Schober, Andreas; Stotz, Stefanie; Neumann, Manuela; Yuan, Xuejun; Grummt, Ingrid; Schütz, Günther; Parlato, Rosanna (The journal of neuroscience, 2011)
The nucleolus represents an essential stress sensor for the cell. However, the molecular consequences of nucleolar damage and their possible link with neurodegenerative diseases remain to be elucidated. Here, we show that nucleolar damage is present in both genders in Parkinson's disease (PD) and in the pharmacological PD model induced by the neurotoxin 1,2,3,6-tetrahydro-1-methyl-4-phenylpyridine hydrochloride (MPTP). Mouse mutants with nucleolar disruption restricted to dopaminergic (DA) neurons show phenotypic alterations that resemble PD, such as progressive and differential loss of DA neurons and locomotor abnormalities. At the molecular level, nucleolar disruption results in increased p53 levels and downregulation of mammalian target of rapamycin (mTOR) activity, leading to mitochondrial dysfunction and increased oxidative stress, similar to PD. In turn, increased oxidative stress induced by MPTP causes mTOR and ribosomal RNA synthesis inhibition. Collectively, these observations suggest that the interplay between nucleolar dysfunction and increased oxidative stress, involving p53 and mTOR signaling, may constitute a destructive axis in experimental and sporadic PD.